2018
DOI: 10.1117/1.nph.5.3.035004
|View full text |Cite
|
Sign up to set email alerts
|

Whole-cortical graphical networks at wakeful rest in young and older adults revealed by functional near-infrared spectroscopy

Abstract: A good understanding of age-dependent changes and modifications in brain networks is crucial for fully exploring the effects of aging on the human brain. Few reports have been found in studies of functional brain networks using functional near-infrared spectroscopy (fNIRS). Moreover, little is known about the feasibility of using fNIRS to assess age-related changes in brain connectomes. This study applied whole brain fNIRS measurement, combined with graph theory analysis, to assess the age-dependent changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
3
8
0
Order By: Relevance
“…GE is also shown to be affected by age. 64 , 71 The GE based findings in this paper are in alignment with the literature, where a decline in GE was observed for neuropsychiatric patients. On average across all stimulus types, there was a 17% reduction in the of migraineurs, 20% of OCD, and 48% of schizophrenics from controls as can be inferred from Table 6 .…”
Section: Discussionsupporting
confidence: 90%
“…GE is also shown to be affected by age. 64 , 71 The GE based findings in this paper are in alignment with the literature, where a decline in GE was observed for neuropsychiatric patients. On average across all stimulus types, there was a 17% reduction in the of migraineurs, 20% of OCD, and 48% of schizophrenics from controls as can be inferred from Table 6 .…”
Section: Discussionsupporting
confidence: 90%
“…Graph theory has been used commonly to examine such brain networks at resting state. In the field of NIRS, task-driven brain activations and GTA-derived network connectivity are often studied separately (Niu et al, 2012 ; Niu and He, 2014 ; Li et al, 2018 ). A recent study revealed that resting-state properties and task-evoked networks in the human brain can have significant correlations with the activation of brain regions during tasks of executive functions (Hu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Graph theory is a renowned mathematical model to study characteristics of a network system (Erdös, 1959 ; Bondy and Murty, 1976 ), and it has been applied to investigate resting state functional connectivity of the human brain as measured with fMRI, Electroencephalography (EEG), and Magnetoencephalographic (MEG) (Salvador et al, 2005 ; Achard et al, 2006 ; Bassett et al, 2006 ; Iturria-Medina et al, 2008 ), as well as fNIRS (Niu et al, 2012 ; Niu and He, 2014 ; Li et al, 2018 ). A recent study demonstrated that based on GTA, brain networks were altered when the human brain transitioned from resting state to task-evoked states (Hu et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations